Rapid Detection of Avian Infectious Bronchitis Virus by Reverse Transcriptase-Loop Mediated Isothermal Amplification - Chandrasekar, A. (Proc Natl Acad Sci India Sect B Biol Sci, 2015)
A reverse-transcription loop mediated isothermal amplification (RT-LAMP) was developed for rapid diagnosis of infectious bronchitis (IB) in poultry by targeting the spike protein 2 gene (S2). RT-LAMP primers were designed for IBV-S2 targets and optimized to run at 60 °C for 45 min. As compared with RT-PCR, RT-LAMP was 100 times more sensitive for IBV-S2 gene. RT-LAMP showed specific amplification with IB viral genome but not with other avian respiratory pathogens due to their mismatching with IBV-S2-RT-LAMP primers. RT-LAMP reaction products were visually detected by the addition of propidium iodide stain. Out of 102 field samples tested for detection of IBV, RT-LAMP detected IBV in 12 samples for S2 gene whereas RT-PCR detected IBV in six samples for S2 gene. The sensitivity of the RT-LAMP was 100 % and the specificity was 94 % for S2 gene. Since the developed RT-LAMP to detect IBV is simple, rapid, sensitive and specific, it can be a useful diagnostic tool for detection of IB in poultry in less equipped laboratories and in field conditions.